Cover Feature: Loops and Cycles at Surfaces: The Unique Properties of Topological Polymer Brushes (Chem. Eur. J. 51/2017). Issue 51 (1st August 2017) - Benetti, Edmondo M.; Divandari, Mohammad; Ramakrishna, Shivaprakash N.; Morgese, Giulia; Yan, Wenqing; Trachsel, Lucca
Abstract : Can the performance of polymer brushes as steric stabilizers, biopassive layers and boundary lubricants be improved? The answer to this intriguing question encompasses the application of polymer grafts presenting different chain topologies, beyond chain linearity. Polymer adsorbates forming loops and cyclic macromolecules yielding cyclic brushes on flat and nanoparticle surfaces generate films with unique physicochemical properties. Benetti and co‐workers review their preparation, characterization and modeling, trying to redefine the paradigm for surface functionalization by polymer grafting. More information can be found in the Minireview by E. M. Benetti et al. onpage 12433 .